Troublemaker - Clements, Andrew, 1949-; Elliott, Mark, 1967- (New York : Atheneum Books for Young Readers, 2011)
When his older brother gets in serious trouble, sixth- grader Clay decides to change his own mischief-making ways, but he cannot seem to shake his reputation as a troublemaker.
730
Keywords: Behavior -- Fiction; Schools -- Fiction; Brothers -- Fiction